Primer on Nephrology - Harber, Mark.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This new edition provides readers with a practice-based approach to all aspects of clinical nephrology. Extensively updated, it offers invaluable practical advice on how to manage specific illnesses and, uniquely, the importance of establishing systems and processes to improve patient safety, enhance the patient pathway and guidance on how to systematically improve clinical governance. A unique feature of this book are the tips and tricks and, suggestions for avoiding common errors based on the vast experience of the authors. In addition, the Editor has collated a list of links to international registries and guidelines as well as selected disease specific organisations, providing both clinicians and patients with access to helpful and recommended resources. Designed and written in a user-friendly fashion, Primer in Nephrology continues to be the definitive reference for practising nephrologists, trainees and non-nephrologist who encounter renal patients in their daily practice.
Assessment of the Renal Patient -- Urine Analysis - Scott R Henderson and Mark Harber -- Imaging in Nephrology -- Kidney Biopsy -- Acute Kidney Injury: Epidemiology and Assessment -- Acute Kidney Injury: Management and Prevention -- Acute renal replacement therapy -- Hepatorenal syndrome -- Common Electrolyte Disorders -- Acid Base Disorders -- Diagnosis and Investigation of the hypertensive patient -- Management of high blood pressure -- Podocytopathies -- Management of the Nephrotic Patient: The overall approach to the patient with Nephrotic Syndrome (NS) -- Management of the Nephrotic Patient: Treatment of ECF volume expansion due to nephrotic syndrome in adults -- Minimal Change Disease and Focal Segmental Glomerulosclerosis -- Membranous Nephropathy -- Membranoproliferative glomerulonephritis and C3 glomerulopathy -- IgA nephropathy and Henoch-Schönleinpurpura -- Systemic Small Vessel Vasculitis -- Goodpasture s or Anti-glomerular basement membrane (GBM) disease -- Systemic lupus erythematosus, antiphospholipid syndrome & the kidney -- Practical immunosuppression guidelines for patients with glomerulonephritis -- Infectious disease and the kidney -- Blood-borne viruses and the Kidney -- Tubulo-Interstitial Nephritis -- Rheumatological conditions and the Kidney -- Multiple myeloma and the kidney -- Amyloidosis -- Thrombotic Microangiopathies -- Sickle cell disease and other haematological disorders involving the Kidney -- Diabetes and the Kidney -- Pregnancy and the Kidney -- Disease of the Renal Vessels -- Urinary tract infection -- Renal Stone Disease -- Congenital anomalies of the kidneys and urinary tract -- Acquired Urinary Tract Obstruction -- Kidney Cancer -- Inherited Renal Tumour Syndromes -- Polycystic kidney disease -- Other Cystic Kidney Diseases -- Genetic disorders of the glomerular basement membrane -- Anderson-Fabry disease and other inherited lipid disorders of the kidney -- Inherited Metabolic Disease -- Dermatology In Kidney Disease -- Chronic kidney disease: Epidemiology and causes -- Chronic kidney disease: management -- Transition -- Anaemia Management in Chronic Kidney Disease -- Chronic Kidney Disease: Mineral and Bone Disorder (CKD-MBD) -- Chronic Kidney Disease: Cardiovascular Complications -- Coagulation in Kidney Disease -- Symptom control and palliative care in advanced CKD -- Nutrition and Kidney Disease -- Pharmacology and the Kidney -- Prevention of Infection in Kidney Patients -- Setting up and running a Haemodialysis Service -- Vascular access- dialysis lines -- Vascular Access- fistulae and grafts -- Complications of maintenance haemodialysis and how to avoid them -- Providing a peritoneal dialysis service -- Peritoneal Dialysis Prescription -- Complications of peritoneal dialysis and how to avoid them -- Assessment of the potential transplant donor -- Assessment of the Potential Transplant Recipient -- Tissue-typing, crossmatch and antibody incompatibility in kidney transplantation -- Surgical aspects of kidney and pancreas transplantation -- Management of the Acute Transplant -- Immunosuppression for Kidney Transplantation -- Infectious complications of transplantation -- Long Term Management of Kidney Transplant Recipients (KTRs) -- International health partnerships -- Appendix. Resources for Patients and Carers and, Physicians -- Videos.
Keywords: Internal medicine; Internal Medicine; Kidney Diseases; Nephrology